Can Firm Size, Business Growth, Capital Structure and Social Responsibility Affect Earnings Response Coefficients? - Jannati Tangngisalu (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2021)
This study aims to analyze the factors that affect the Earnings Response Coefficient. The focus of this research is 52 companies from 170 manufacturing companies listed on the Indonesia Stock Exchange. Sampling using the purposive sampling method by considering the presence of data outliers. The data was collected using documentation techniques (secondary data) and analyzed through several stages, including descriptive analysis, inferential analysis, classical assumption test (consisting of normality test, multicollinearity test, and heteroscedasticity test) multiple linear regression analysis, hypothesis testing (simultaneous test). Partial and coefficient of determination test). The results showed that this study showed that company size, company growth, capital structure, and corporate social responsibility had a positive but not significant effect on the Earnings Response Coefficient. Theoretically, this study implies that it can provide additional knowledge, as a source of information, and as a contribution to ideas in terms of developing accounting disciplines, financial management, and contributing to research development, especially regarding company size, company growth, capital structure, and CSR to ERC as input and additional references for readers. Practically, the results of this study can be used by investors who want to invest in manufacturing sector companies listed on the Indonesian stock exchange to pay attention to the variables that affect ERC